Bactericidal Properties of Blackened Titanium Dioxide on Glass Filter: A Proof of Concept for Water Decontamination - Currie, Sara (Université d'Ottawa / University of Ottawa, 2025)
Water scarcity remains a pressing global challenge, disproportionately affecting rural communities lacking access to effective water treatment systems. This thesis explores the development and optimization of a solar-powered water purification technology employing blackened titanium dioxide (bTiO₂) as a photocatalyst to address bacterial contamination. This work builds on the "Water Project," a collaborative initiative aimed at sustainably purifying river water in Kenya using abundant sunlight for community-scale applications. Beyond sunny regions, this technology holds great potential in areas like northern Canada or anywhere under a boil water advisory, where white LEDs can serve as an effective substitute for sunlight. Heterogeneous bTiO₂, synthesized directly onto glass filter supports, demonstrates robust photocatalytic activity under white light, facilitating the generation of reactive oxygen species (ROS) for bacterial inactivation. The material's properties, including extended spectral absorption (300-800 nm) and reduced bandgap energy (from 3.3 eV to 2.18 eV), enable efficient solar-driven disinfection. Two bacterial strains, Escherichia Coli (Gram-negative) and Staphylococcus Aureus (Gram-positive), were chosen as representative contaminants due to their prevalence in Kenyan river water and health implications. A key innovation in this study is the development and application of a fluorescence-based viability assay using PicoGreen. This novel method offers rapid and reliable evaluation of bacterial viability within 10 minutes, significantly faster than traditional colony counting methods. Importantly, the research uncovers a novel dependency of PicoGreen fluorescence on the bacterial inactivation pathway. The assay is highly sensitive to lysis-mediated inactivation, where cellular membranes are disrupted, but demonstrates limited fluorescence response with apoptotic cells, where ROS- mediated DNA damage and fragmentation occur without significant loss of membrane integrity. While PicoGreen has been shown to produce false negatives under certain conditions, it has never demonstrated false positives, ensuring that bacterial inactivation is never overestimated. This reliability makes the method worthy of further study, as a false positive would undermine the validity of disinfection processes, whereas a false negative only highlights the need for further refinement. These findings provide critical insights into the mechanism-specific applicability of fluorescence-based quantification methods. This thesis employs batch and flow systems to assess bacterial inactivation, with outcomes quantified using the PicoGreen assay. The thesis achieved notable bacterial inactivation with bTiO2, particularly during Flow 3.0 tests that incorporated oxygen bubbles to enhance turbulence and ROS generation. E. Coli inactivation reached 99.8 %, exceeding the WHO standard of 99 % within 30 minutes, while S. Aureus achieved 98.5 %, narrowly missing the benchmark by 0.5 %. However, the spatial limitations of batch systems prompted the development of three flow systems, including a single-pass configuration with gas bubbling to enhance turbulence and ROS availability. Flow systems significantly improve bacterial interaction with the catalyst, achieving two-log bacterial reductions within 30 minutes, meeting World Health Organization (WHO) guidelines for water disinfection. Beyond establishing that our new catalyst can kill bacteria under white light and flow conditions, we also investigated mechanistic insights into bacterial inactivation and the behavior of PicoGreen using fluorescence lifetime imaging microscopy (FLIM). Results indicate that ROS-induced oxidative stress is the primary inactivation pathway, leading to cellular damage and membrane disruption. Scanning electron microscopy (SEM) imaging highlights the importance of flow systems in mitigating biofilm formation on the catalyst surface. This work advances the application of solar-activated photocatalysis for sustainable water purification. The findings underscore the potential of bTiO₂ in delivering accessible, efficient, and environmentally friendly solutions to global water challenges, while the novel fluorescence assay contributes to streamlined monitoring of water quality in real-time applications.
Keywords: Black Titanium Dioxide; Water Decontamination; Proof-of-Concept